Immigrant earnings: a longitudinal analysis - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2005)
This paper uses the Longitudinal Survey of Immigrants to Australia to analyze the determinants of the level and growth in earnings of adult male immigrants in their first 3.5 years in Australia. The theoretical framework is based on the immigrant adjustment model, which incorporates both the transferability of immigrant skills and selectively in migration. The cross-sectional and longitudinal analyses generate similar findings. The level and relative growth of earnings are higher for immigrants with higher levels of skill and who are economic/skills tested migrants, as distinct from family based and refugee migrants. The analysis indicates that immigrant economic assimilation does occur and that in these data the cross-section provides a good estimate of the longitudinal progress of immigrants. The findings are robust across statistical techniques.
Keywords: F22; J31; J61; 330; immigrants; wages; longitudinal survey; inertia model; Australia; Männliche Arbeitskräfte; Bildungsertrag; Lohn; Soziale Integration; Australien